Canopies at public transport stops in Belgrade: an example of open public micro-spaces in the city - Maksić Mulalić, Milica (Arhitektura i urbanizam, 2023)
"Micro-spaces" - small-scale public city spaces - represent an important element in the structure of the city both functionally and aesthetically. Due to their small scale, their importance is often overlooked by experts and investors. The paper describes the concept of canopies at public transport stops in Belgrade, which were created in the period from 2007 to the present day. By multiplying the basic type and its variations, a recognizable element of the city image is built. By upgrading the basic project, introducing additional elements from the repertoire of modern design, "green" constructions, "smart" technologies, energy efficiency, etc. this form of urban space would be additionally affirmed and contribute not only to the comfort of users, the creation of the identity of the city and public city transport, but also to general interests such as safety, health and environmental protection.